2018
DOI: 10.1111/1346-8138.14489
|View full text |Cite
|
Sign up to set email alerts
|

pH in nature, humans and skin

Abstract: The pH plays an important physiological role in nature and humans. pH varies from 1 to 8 in human organs with tight regulation in blood and epithelia of barrier organs. The physiological pH of the stratum corneum is 4.1-5.8 and several mechanisms contribute to its formation: filaggrin degradation, fatty acid content, sodium-hydrogen exchanger (NHE1) activation and melanosome release. First, the acidic pH of the stratum corneum was considered to present an antimicrobial barrier preventing colonization (e.g. by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
273
2
18

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(332 citation statements)
references
References 111 publications
4
273
2
18
Order By: Relevance
“…In line with results of this study, our previous study with the same cosmetic products utilizing two different models (a short‐term chemical damage and mechanical damage of epidermal barrier after long‐term treatment) could clearly show that pH is important and an independent factor influencing epidermal barrier . Finally, it is also important to note that not only aging skin, but also diseased skin (atopic dermatitis, psoriasis or ichthyosis vulgaris) have been linked to increased pH …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In line with results of this study, our previous study with the same cosmetic products utilizing two different models (a short‐term chemical damage and mechanical damage of epidermal barrier after long‐term treatment) could clearly show that pH is important and an independent factor influencing epidermal barrier . Finally, it is also important to note that not only aging skin, but also diseased skin (atopic dermatitis, psoriasis or ichthyosis vulgaris) have been linked to increased pH …”
Section: Discussionsupporting
confidence: 89%
“…46,47 Finally, it is also important to note that not only aging skin, but also diseased skin (atopic dermatitis, psoriasis or ichthyosis vulgaris) have been linked to increased pH. 48 Normalization of skin pH following exogenous acidification is improving epidermal permeability barrier homeostasis, SC integrity/cohesion and anti-inflammatory function 12,13 and reduces damage to exogenous stress (SDS) as shown in this study. Moreover, normalization of an increased pH improves the activity of pH-dependent enzymes involved in epidermal differentiation 2,49 differentiation.…”
Section: Discussionmentioning
confidence: 51%
“…42 Beyond the impaired barrier function and increased skin diffusivity, the findings of earlier studies showing that increased skin surface pH, as found in AD, results in the activation of proteases involved in the processing of the pro-forms of the IL-1 cytokines in the epidermis, provide another possible explanation for the enhanced barrier responses in atopic compared to healthy skin, observed in the present om-TRIT. 35,[43][44][45] As the volunteers in the study were not genotyped, our results do now allow for conclusions on the influence of FLG mutation carrier status on the outcomes of repeated exposure to npropanol in atopic or healthy skin.…”
Section: Discussionmentioning
confidence: 94%
“…Biophysical parameters are strongly influenced by intrinsic and extrinsic factors like age, sex, race, circadian rhythm, season, exercise and acclimatization period; 22,95,99,100,[124][125][126][127][128][129][130][131] therefore data collection is inherently difficult to standardize.…”
Section: Discussionmentioning
confidence: 99%